The Implementation of Artificial Intelligence (AI) Chat GPT in English Language Learning at SDIT Plus Usman Bin Ali Medan - Siska Wulandari Lubis; Sumarsih; Rahmad Husein (Nusantara Science and Technology Proceedings, 2023)
The body of your This study was conducted and found that English teachers knew about the use of Chat GPT. On the other hand, the delivery of material seemed rigid and monotonous. This study aimed to find the use of Chat GPT in preparing lesson plans, implementing lessons, and evaluating English learning at SDIT Plus Usman Bin Ali. The method used is descriptive qualitative research, which aims to provide a detailed description of a particular phenomenon or setting. The results of this study illustrate that the use of Chat GPT in Preparing English Learning Plans at SDIT Plus Usman Bin Ali does not fully use Chat GPT, due to several technical reasons. The use of Chat GPT in English Language Learning Implementation at SDIT Plus Usman Bin Ali using Chat GPT is used to find in-depth information about learning methods. The use of Chat GPT in English Learning Evaluation at SDIT Usman Bin Ali is not used.